PENDIDIKAN KESEHATAN MELALUI MEDIA ONLINE TERHADAP PENGETAHUAN DAN PERILAKU PENCEGAHAN KANKER SERVIKS PADA WUS DI SIKKA - Regina Ona Adesta; Emanuela Natalia Nua (Jurnal Ilmu Keperawatan Maternitas, 2021)
Background: Reproductive health problems faced by women today are increasing infections in the reproductive organs, which in turn lead to cancer, one of that is cervical cancer. Lack of awareness to prevent cervical cancer is one of the problems that often occur in the health of Fertile Age Women. The effort that needs to be done to prevent cervical cancer is by providing health education through online media, to increase the knowledge and behavior of Fertile Age Women in preventing cervical cancer. The purpose of this research is to determine the effect of health education on early detection of cervical cancer through online media on the knowledge and behavior of Fertile Age Women in cervical cancer prevention in Nanga Public Health Center of Sikka Regency. Method of this research used a pre-experimental design with one group pre-test post-test design method, using a consecutive sampling technique, with as many as 199 respondents. The data collection tool used a questionnaire. Data were analyzed through the Wilcoxon Signed Rank Test with SPSS for windows version 20. Results of this research indicated that there was a very significant effect on the provision of health education through online media on early detection of cervical cancer on knowledge and behavior of cervical cancer prevention of Fertile Age Women in Nanga Public Health Center of Sikka Regency with a p-value of 0.000 (p < 0.05). Providing health education on early detection of cervical cancer with online media can increase knowledge and behavior of cervical cancer prevention of Fertile Age Women. It is hoped that the public health center will provide health education with online media, to support the prevention of covid-19 transmission and to increase the knowledge and behavior of Fertile Age Women in cervical cancer prevention.